Harnessing monoterpenes and monoterpenoids as weapons against antimicrobial resistance - Kong, Amanda Shen-Yee; Lim, Swee-Hua Erin; Cheng, Wan-Hee; Yuswan, Mohd Hafis; Tan, Ngai-Paing; Lai, Kok-Song (Sciendo, 2025)
Antimicrobial resistance (AMR) poses a formidable challenge in global healthcare, driving the exploration of natural products for novel antimicrobials. Among these, essential oils (EOs) derived from medicinal plants are rich sources of diverse bioactive compounds. Monoterpenes and monoterpenoids, critical constituents of EOs, have emerged as promising agents in combating multidrugresistant (MDR) pathogens. This review analyzed recent literature on the efficacy of monoterpenes against AMR, highlighting their broad-spectrum activity and potential as alternative therapeutic options for MDR infections. Mechanistic insights reveal their ability to disrupt cell membranes, inhibit biofilm formation, and modulate gene expression linked to virulence and resistance, thereby reducing microbial viability through alterations in membrane potential, enzymatic activity, and genetic regulation. Synergistic interactions between monoterpenes and conventional antibiotics are also elucidated. Innovative approaches in monoterpene research are explored, although challenges such as resistance, limited solubility, volatility, and potential toxicity are acknowledged, emphasizing the need for advanced formulation strategies and interdisciplinary research. The synergy observed with conventional antibiotics, coupled with their ability to target specific microbial resistance mechanisms, underscores the potential of monoterpenes in combating antibioticresistant infections. Future investigations should prioritize optimizing monoterpenes' therapeutic properties and assessing their safety profiles to fully exploit their potential in addressing AMR.